Punta di Zambrone I: 1200 BCE - a Time of Breakdown, a Time of Progress in Southern Italy and Greece - Jung, Reinhard (Verlag der Österreichischen Akademie der Wissenschaften, 2021)
This monograph presents a major part of the scientific results of the archaeological excavations at the Bronze Age settlement site of Punta di Zambrone on the Tyrrhenian coast of Calabria (southern Italy), conducted from 2011 to 2013 in an Italian-Austrian cooperation. The book is the first in a series dedicated to the final publication of those excavations and focuses on the later part of the settlement history (13th-12th cent. BCE). Major topics include the topography of the site (including a harbour bay), itschronology, investigations into the economic basis of the Bronze Age society and its local, regional and interregional interactions.